The Romans in North Africa [videorecording (DVD)] : a journey back in time - Hurst, Henry; Wilson, Roger; Mattingley, David (Lost treasures of the ancient world., 2006)
Features the major Roman dwellings in the North African region, with exciting footage of Carthage, this unique underground city of Bulla Regia and the recently discovered Chimtou.